ANALISIS TINGKAT KESEJAHTERAAN MASYARAKAT DAMPAK PEMBERIAN KREDIT (Studi Pada Debitur PD. BPR NTB Sumbawa) - Reninta Sulistiyawati; Ika Fitriyani; K Kurniawansyah (Jurnal Ekonomi & Bisnis, 2023)
This study aims to examine the impact of the provision of credit by PD. BPR NTB Sumbawa on the welfare of debtor customers through per capita income indicators. This research is a comparative study to compare the income levels of customers before and after receiving working capital loans from PD. BPR NTB Sumbawa. The type of data used is quantitative data in the form of customer income before and after receiving working capital loans from PD. BPR NTB Sumbawa obtained directly from customers. The research subjects were customers who received working capital loans from PD. BPR NTB Sumbawa in 2022, totaling 37 people. Data collection was carried out through structured interviews using a list of questions that had been prepared by the researcher to obtain relevant data related to the research object. Data analysis techniques were carried out using the two-average difference test method, including calculating the difference in income, standard deviation, and one variable test. Based on the results of the research that has been done, it can be concluded that there are differences in the average income of respondents before and after receiving working capital loans from PD. BPR NTB Sumbawa. There was an increase in the income of customers who were used as respondents after receiving working capital loans from PD. BPR NTB Sumbawa of Rp. 81,432,081.04/month.